Internet and surveillance : the challenges of Web 2.0 and social media - Fuchs, Christian, 1976- (Routledge studies in science, technology, and society, 2012)
The Internet has been transformed in the past years from a system primarily oriented on information provision into a medium for communication and community-building. The notion of "Web 2.0", social software, and social networking sites such as Facebook, Twitter and MySpace have emerged in this context. With such platforms comes the massive provision and storage of personal data that are systematically evaluated, marketed, and used for targeting users with advertising. In a world of global economic competition, economic crisis, and fear of terrorism after 9/11, both corporations and state institutions have a growing interest in accessing this personal data. Here, contributors explore this changing landscape by addressing topics such as commercial data collection by advertising, consumer sites and interactive media; self-disclosure in the social web; surveillance of file-sharers; privacy in the age of the internet; civil watch-surveillance on social networking sites; and networked interactive surveillance in transnational space. This book is a result of a research action launched by the intergovernmental network COST (European Cooperation in Science and Technology)